Epoxidation of Jatropha methyl esters and evaluation of its properties - Derahman, Aishah (2017)
Epoxides are known to have many applications in various industries because it contains highly reactive materials. Depletion of current resources is prompting researchers to find a replacement that is highly available. Jatropha seed oil is currently gaining attention because of its availability and versatility. The objectives of this study are to investigate various factors affecting production of bio-epoxides from Jatropha methyl esters (JME) through epoxidation method, to optimize production of bio-epoxides using RSM and to characterize bio-epoxides in term of physicochemical and spectroscopic characterization. JME was first synthesized using two-step transesterification method from crude Jatropha oil (CJO). Factors affecting epoxidation methods; temperature and time, molar ratio of hydrogen peroxide and acetic acid to unsaturation and catalyst loading were investigated. Physicochemical properties of JME were identified; iodine value was found out to be 107.7. Highest percentage yield of JME obtained is 90.6 with total reaction time of 4 hours. Obtained JME further used in epoxidation process. Based on RSM results, optimum temperature 70 °C, molar ratio of hydrogen peroxide 1.9 mol, molar ratio of acetic acid 0.75mol and reaction time of 3.2 hours. Maximum relative conversion to oxirane was 92.8. Spectroscopic characterization of epoxy resin was conducted using FTIR and NMR. In FTIR, unsaturation peaks were present at 3008.67 cm-1 in CJO and JME and this peak diminished in epoxidized JME and oxirane rings surface at 825 and 843 cm-1.1H NMR analysis showed unsaturation peaks in between 5.27-5.32 and oxirane at 2.85 and 2.97.13C NMR analysis presents unsaturation peaks in between 127.94- 130.13 and oxirane at 56.88 ppm. In addition, blends of bio-epoxides with synthetic epoxy resin were prepared and subjected to flexural and tensile strength test. Bioepoxides and synthetic epoxy resins blends had low tensile and flexural strength and were not suitable for applications as alternative to synthetic epoxy resin . However, it may find other application as biolubricants or polymeric coatings.